Sosialisasi Pengelolaan Keuangan Daerah Di Kabupaten Penajam Paser Utara - Akbar Lufi Zulfikar; Selly Swandari; Swadia Gandhi Mahardika (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Effective and efficient regional financial management requires legal regulations that are outlined in statutory regulations (legal aspects) so that they have a juridical-normative and juridical-sociological nature. Legal regulations for regional financial management are carried out in accordance with the aim of establishing a legal regulation, namely: "to provide order." , stability, and justice. The existence of law is something that is very substantial theoretically and paradigmatically for the fabric of regional financial management in all segments of state government administration. In principle, it can be said that through legal instruments, regional financial management is expected to have and guarantee the establishment of a condition that contains content, certainty and justice.